Genetic adaptation to climatic risks: crowdsourcing farmers’ preferences for crop varieties - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Farmers are often not able to quickly access and adopt new crop varieties that are developed and tested by scientists. Biodiversity International, supported by CCAFS, is working with farmers to evaluate crop varieties as part of the ‘Seeds for Needs’ project. This project aims to expose local farmers to diverse crop varieties and increase their knowledge and familiarity about different traits and options. This participatory approach allows farmers to grow a range of crop varieties on their ﬁelds and rank them according to performance.